PENGARUH DIGITAL SCRAPBOOK BERBASIS KEARIFAN LOKAL TERHADAP LITERASI BUDAYA SISWA KELAS IV SD N 69 PALEMBANG - Syalsyabilah, Puji; Murjainah, Murjainah; Suriadi, Aan (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
This study aims to determine the effect of a digital scrapbook based on local wisdom on the cultural literacy of fourth-grade students at SD N 69 Palembang. The research method used is a quantitative true-experimental design with a post-test only control group. The population of this study consists of fourth-grade students at SD N 69 Palembang, with class IVA serving as the control group and class IVB as the experimental group. The results of the normality test with a significance level of ≥ 0.05 indicate that the experimental class achieved a result of 0.200 ≥ 0.05, and the control class also received a result of 0.200 ≥ 0.05, with an average score of 65.3 for the control class and an average score of 85.12 for the experimental class. Based on the results of the independent sample t-test conducted using SPSS, the significance (sig.) value is 0.000 with a significance level of α = 0.05. Therefore, it can be stated that sig. 0.000 < 0.05, or the calculated value ≥ ttable= 5.128 ≥ 1.690. Based on the decision criteria, H0 is rejected and Ha is accepted, thus proving that the digital scrapbook based on local wisdom has an impact on the cultural literacy of students.